Green Investments and Worker Voice - Davide Bisi; Fabio Landini; Riccardo Rinaldi (Global Labor Organization (GLO), 2025)
The interaction between organised employee representation (ER) and firms' engagement in the green transition remains insufficiently understood. Theoretically, two opposing mechanisms may operate. In the bargaining view, representation can slow green investments by increasing adjustment costs and exposing firms to rent-seeking pressures. In contrast, the employee voice perspective holds that ER enables sustainability by facilitating information exchange, eliciting workers' environmental preferences, and supporting joint problem-solving when organisational adaptation is required. We test these predictions using survey and administrative data from nearly 2,000 firms in Emilia-Romagna. Firms with ER are systematically more likely to pursue green investments, especially in climate mitigation, water use, circularity, and pollution prevention. These results also hold when accounting for the endogeneity of ER via IV. Consistent with the voice mechanism, the association between ER and green investments is stronger in firms employing younger and more educated workers, who are more likely to hold proenvironmental preferences and contribute specialised knowledge relevant for organisational change. Taken together, our findings challenge the view that organised labour inhibits the green transition. Instead, ER emerges as a strategic policy lever that can foster decarbonisation pathways that are technologically feasible, socially negotiated, and democratically anchored at the workplace level.
Keywords: J50; O33; Q50; 330; worker voice; employee representation; sustainability; climate change; green investments